Study to Determine the Effect of Diaper-Based Wound Care Method in Reducing Wound Contamination Period in Patients Suffering from Perianal Burn Wound - Chandrashekhar Subhash Chalwade; Abhijeet D. Sawant; Ishita Katyal (Indian Journal of Plastic Surgery)
Background Local wound care in perianal burn wounds is difficult owing to the risk of contamination from fecal soiling. The problem is aggravated in small children and bedridden critical patients who are unable to convey passage of stools. We used diaper-based wound care to reduce contamination.